What makes nature-based interventions for mental health successful? - Dan Bloomfield (BJPsych International, 2017)
Nature-based interventions for mental health are beginning to become more common in the UK. The evidence for their usefulness is building. Taking the ‘A Dose of Nature’ project in the south-west as an example, factors for making such interventions a success are described.